Writing Language in the Public Space of Universitas Andalas: A Linguistic Landscape Study - Hamidi, Ahmad; Yusuf, Muhammad; Aslinda, Aslinda (Universitas Andalas, 2025)
This study examines written language errors in public spaces at Universitas Andalas as a response to a linguistic paradox: the international recognition of Indonesian—marked by its designation as an official language of UNESCO—and persistently disordered domestic practices, particularly within higher education contexts. The objectives of the study are to identify the forms and degrees of dominance of linguistic errors and to interpret their implications for language practices and institutional image. Employing a descriptive–analytical approach, the study applies error analysis to 30 data sources containing 151 linguistic errors. The results reveal that orthographic errors are the most dominant, accounting for 73.51% of all cases, followed by lexical choice errors (9.93%), sentence-level errors (5.30%), logical errors (4.64%), and phrase- and clause-level errors, each comprising 3.31%. These findings suggest that linguistic issues in public spaces are predominantly microstructural and technical in nature, reflecting a low adherence to the norms of written Indonesian. This phenomenon suggests a lack of normative awareness among educated communities. The study recommends strengthening the role of academic institutions in monitoring language use in public spaces and utilizing artificial intelligence (AI) technologies in conjunction with human linguistic expertise to enhance the quality of public texts, thereby contributing to the elevation of Indonesian as a national language.